IMPROVING STUDENTS LEARNING OUTCOMES ON CIRCLE EQUATION MATERIAL USING GEOGEBRA SOFTWARE - I Wayan Widana; Brigita Diny Laksitasari (Indonesian Journal of Educational Development (IJED), 2023)
This study aims to describe learning using GeoGebra software on circle equations material that can improve students learning outcomes of class XI MIPA5 SMAN 1 Mengwi. The research method used is Class Action Research (CAR) which consists of four stages, namely planning, implementation, observation, and reflection. The subject of this study is all students of class XI MIPA5 SMAN 1 Mengwi, while the object of research is the entire process and results of mathematics learning using GeoGebra software on circle equation material as an effort to improve students learning outcomes of the class. The data collection techniques used are observation, interviews, and tests. This research was carried out in two CAR cycles. The results showed that the application of mathematics learning using GeoGebra software on circle equations material can improve the learning outcomes of class XI MIPA5 SMAN 1 Mengwi students. This is shown by the average student learning outcomes in the final test I, which is 83 with a classical completion percentage of 75% increasing to 90 in the final test II with a classical completion percentage of 89%.